Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/nep.12266
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Niban in renal interstitial fibrosis

Abstract: Niban decreased in renal tubular cells of patients of obstructive nephropathy, UUO rats and TGF-β1 stimulated HK-2 cells. Suppressing Niban increases apoptosis in HK-2 cells. Niban may be associated with apoptosis of HK-2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Niban is overexpressed in several cancers and modulate cell death through regulation of its expression and phosphorylation [62][63][64][65][66]. The antiapoptotic activity of Niban is governed by Akt-dependent phosphorylation as it disrupts p53-containing protein complex under UV-stress [28] and experimental overexpression of the protein alone failed to diminished apoptosis in tumor cells [67]. Depending on the cell type and the nature of the stimuli, cytotoxic concentration of ATP either inhibits [68,69] or stimulates Akt phosphorylation [39,70].…”
Section: Discussionmentioning
confidence: 99%
“…Niban is overexpressed in several cancers and modulate cell death through regulation of its expression and phosphorylation [62][63][64][65][66]. The antiapoptotic activity of Niban is governed by Akt-dependent phosphorylation as it disrupts p53-containing protein complex under UV-stress [28] and experimental overexpression of the protein alone failed to diminished apoptosis in tumor cells [67]. Depending on the cell type and the nature of the stimuli, cytotoxic concentration of ATP either inhibits [68,69] or stimulates Akt phosphorylation [39,70].…”
Section: Discussionmentioning
confidence: 99%
“…Activin is a recently discovered member of the transforming growth factor (TGF)-β superfamily, and TGF-β, which is well recognised as an important factor for fibrosis, is a marker of transdifferentiation of tubular epithelial cells into fibroblasts. Activin can promote the differentiation of renal tubular epithelial cells, promote the proliferation of interstitial cells, and has a role in fibrosis of the renal interstitium [20]. It was shown that there was almost no expression of activin in the kidneys of healthy adults, and the expression of activin in renal tissue in patients with ischaemia-reperfusion injury was significantly increased [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well‐known that some members of the FAM129 proteins (to which BCNP1 or FAM129C belongs) such as Niban (FAM129A) are indeed involved in cancer. For example, Niban was found to be up‐regulated in renal carcinoma 2, 7, 8 in renal interstitial fibrosis 6, head and neck squamous cell carcinoma and squamous dysplasia 9, and also in thyroid tumours and Hashimoto's thyroiditis 10. Sun et al .…”
Section: Introductionmentioning
confidence: 99%
“…Many components of the PI3K signalling pathways are frequently altered in a broad spectrum of human cancers [5]. Currently, there are multiple clinical trials studying the role of inhibitors involving PI3K and other kinases in the signalling pathways in cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%